Mechanisms behind diversity and ecosystem functioning relationships - the insights from observational and manipulative studies in grassland communities - Lisner, Aleš (Jihočeská univerzita, 2023)
This thesis focuses on the relationship between diversity and two commonly used ecosystem functions - productivity and its stability. The thesis tries to assess the problematics from different perspectives using large-scale observational studies and small-scale manipulative experiments to better understand which mechanism create observed patterns. High emphasis is put on the methodological aspects and potential theoretical or practical issues arising from experimental setting and data collection. More specifically, the thesis starts with description and critical evaluation of patterns observed at bigger spatial scales and across multiple sites (Chapter I). Then continue with detailed small-scale experimental approaches and assessment of mechanism driving relationship between diversity, productivity and stability of communities (Chapter II and III). Further, the thesis digs into bigger detail focusing on which plant characteristics define abundance patterns of individual species, which translates into productivity (Chapter IV). Finally, it elaborates on common issues related to vegetation data collection and their subsequent analysis (Chapter V).
Mechanisms behind diversity and ecosystem functioning relationships - the insights from observational and manipulative studies in grassland communities
Keywords: diversity; productivity; ecosystem functioning; traits; stability; sampling error